FUNDAMENTAL RIGHTS AND GUARANTEES APPLICABILITY OF THE RIGHT TO LIFE OF THE UNBIRTH (CIPEEX, 2025)
Life is a fundamental right owed to any person, as provided by the Constitution itself. Even though it is a non-absolute right and can be relativized in some cases, it remains the most fundamental. Because it is the guarantor of all other fundamental rights and guarantees that support the Brazilian Magna Carta. As a result, there is a debate about the rights that belong to unborn children. Faced with a long debate about the beginning of human life, to define where the protection of the life of an unborn child should begin, so that all their other rights and guarantees can be preserved by the State and by society itself, such as the right to dignity , inheritance, health, among others. Analyzing how the protection of the unborn child has been in court, the main decisions and how scholars deal with the subject. Thus, the following research will be carried out in search of a better understanding of the rights of the unborn child.
Keywords: life; law; unborn child; Protection; Human dignity